2011
DOI: 10.1016/j.jacc.2010.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Parental History and Myocardial Infarction Risk Across the World

Abstract: A parental history (PH) of coronary heart disease (CHD) is consistently associated with a higher risk of the development of CHD in several studies (1-9). It is generally accepted that this association is explained by a combination of predominantly known risk factors and genetic variants (10). Although many studies show that risk factors and genetic polymorphisms are significantly associated with myocardial infarction (MI), these studies fail to show how these associations may explain the relationship between P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 32 publications
10
83
0
5
Order By: Relevance
“…A recent multicenter prospective study based on the APPROACH registry reported FHxCAD patients were more likely to be on cardiovascular medications such as aspirin, beta-blockers, statins, angiotensin converting enzyme inhibitors and angiotensin receptor blockers (5). Also, FHxCAD patients are more likely to be physically active, and consume healthy daily diet consisting of fruits and vegetables (8). In addition, patients with positive family history are more aware of future cardiovascular risk and also present earlier for the management of important modifiable risk factors such as hypertension (9).…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter prospective study based on the APPROACH registry reported FHxCAD patients were more likely to be on cardiovascular medications such as aspirin, beta-blockers, statins, angiotensin converting enzyme inhibitors and angiotensin receptor blockers (5). Also, FHxCAD patients are more likely to be physically active, and consume healthy daily diet consisting of fruits and vegetables (8). In addition, patients with positive family history are more aware of future cardiovascular risk and also present earlier for the management of important modifiable risk factors such as hypertension (9).…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining the family history of CHD and hypercholesterolaemia is important to enhance the phenotypic diagnosis [6,26,[34][35][36], but this information is often neglected or may not be available in practice [25,37]. The presence of tendon xanthomata in early life with marked elevation in plasma LDL-cholesterol establishes the diagnosis of severe FH [32], but sitosterolaemia should also be excluded with plasma phytosterol and DNA testing [38]; in adults, tendon xanthomata with normal plasma cholesterol may be seen in sitosterolaemia and cerebrotendinous xanthomatosis.…”
Section: Diagnosis and Assessment Of Adultsmentioning
confidence: 99%
“…[33][34][35] The strong effect of genetics is further supported by a 50% increase in risk of CHD for a sibling or one parent with CHD after 50 years of age to a 6-fold increase in risk with CHD before age 50 in both parents. 36 Over the past decade, 58 independent loci associated with CHD have been identified by genome-wide association studies, with the most recent analysis including 60 801 cases. 37 The majority of the independent loci have a minor allele frequency >5%, with less common alleles unlikely to have substantial utility in prediction.…”
Section: Genetic Markers Of Riskmentioning
confidence: 99%